2021
DOI: 10.1111/myc.13320
|View full text |Cite
|
Sign up to set email alerts
|

Axillary Digital Thermometers uplifted a multidrug‐susceptible Candidaauris outbreak among COVID‐19 patients in Brazil

Abstract: Objectives To describe the first outbreak of Candida auris in Brazil, including epidemiological, clinical and microbiological data. Methods After the first Candida auris ‐colonised patient was diagnosed in a COVID‐19 ICU at a hospital in Salvador, Brazil, a multidisciplinary team conducted a local C . auris prevalence investigation. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 35 publications
0
67
0
3
Order By: Relevance
“…Another aspect that deserves special consideration is the importance of environmental contamination. In the setting of a COVID-19 ICU, fomite transmission, which is challenging both to recognize and to eradicate [97], was identified to be responsible for nosocomial transmission of KPC-Kp in Germany (ventilators), and in Brazil C. auris (axillary thermometers) [85]-and it is a well-known source of nosocomial outbreaks of MRSA [15] and CRAB [12]. In New Jersey, during a peak of COVID-19 cases in April 2020, Perez et al reported several unintentional changes in standard infection prevention and control (IPC) practices, which included a temporary discontinuation of appropriate PPE use, environmental cleaning and prolonged use of ventilator circuits and suctioning catheters [98].…”
Section: Discussion Disruption Of Infection Control Measures and Antimicrobial Stewardship In Covid Icusmentioning
confidence: 99%
See 1 more Smart Citation
“…Another aspect that deserves special consideration is the importance of environmental contamination. In the setting of a COVID-19 ICU, fomite transmission, which is challenging both to recognize and to eradicate [97], was identified to be responsible for nosocomial transmission of KPC-Kp in Germany (ventilators), and in Brazil C. auris (axillary thermometers) [85]-and it is a well-known source of nosocomial outbreaks of MRSA [15] and CRAB [12]. In New Jersey, during a peak of COVID-19 cases in April 2020, Perez et al reported several unintentional changes in standard infection prevention and control (IPC) practices, which included a temporary discontinuation of appropriate PPE use, environmental cleaning and prolonged use of ventilator circuits and suctioning catheters [98].…”
Section: Discussion Disruption Of Infection Control Measures and Antimicrobial Stewardship In Covid Icusmentioning
confidence: 99%
“…During the ongoing COVID-19 pandemic, the large number of COVID-19 patients requiring critical care and the prolonged use of personal protective equipment (PPE) by the healthcare personnel may have inadvertently mediated a silent dissemination of this fungal pathogen [83,84]. For instance, in an epidemiological investigation conducted in Brazil, Nobrega de Almeida et al found that axillary monitoring thermometers may facilitate the dissemination of C. auris in hospital settings [85].…”
Section: Multidrug Resistant Candida Spp In Covid-19-associated Candidemiamentioning
confidence: 99%
“…Nine case reports and seven case series were retrieved [108][109][110][111][112][113][114][115][116][117][118][119][120][121][122][123], together reporting 41 cases of candidemia (Table 4; detailed information about the individual studies is given in Table S4). The median time from ICU admission or intubation to the diagnosis of candidemia was 13.5 days (IQR 7.5-29.5), and more than 80% of the patients had an indwelling vascular catheter, received broad-spectrum antibiotics, and underwent mechanical ventilation before its onset.…”
Section: Case Reports and Case Seriesmentioning
confidence: 99%
“…Critically, C. auris could be easily spread because of the COVID-19 pandemic [ 35 ]. After the first C. auris -colonized case was diagnosed in a COVID-19 patient in ICU at a hospital in Salvador, Brazil, a multidisciplinary team conducted a local C. auris prevalence investigation [ 36 ]. Remarkably, findings revealed that among body swabs collected from 47 patients, eight samples from the axillae were positive for C. auris .…”
Section: Fungal Infections As a Co-morbidity Of Covid-19mentioning
confidence: 99%
“…Contaminated axillary monitoring thermometer helped to C. auris dissemination. Re-use of these devices must imply a careful disinfection or they should be replaced by other temperature monitoring methods [ 36 ]. Moreover, in 2020, the Florida Department of Health was alerted to three C. auris bloodstream infections and one urinary tract infection (UTI) in four patients with COVID-19 who had received care in the same COVID-19 ICU ward [ 37 ].…”
Section: Fungal Infections As a Co-morbidity Of Covid-19mentioning
confidence: 99%